English in Southeast Asia : varieties, literacies and literatures - Prescott, David (David Lochmohr); Kirkpatrick, Andy; Azirah Hashim; Martin, Isabel (Isabel Pefianco) (Cambridge Scholars Pub., 2007)
This book represents a new publishing venture in terms of its range of concerns with regard to English in Southeast Asia. The chapters in the volume reflect the interests and themes of the annual Conferences on English in Southeast Asia held since 1996 among participating universities from nine countries: Malaysia, Singapore, Brunei, Philippines, Australia, Hong Kong, Thailand Indonesia and New Zealand. This is believed to be the first time that such diversity and coverage has been published ...